Effects of Different Formulations of Glyphosate on Rumen Microbial Metabolism and Bacterial Community Composition in the Rumen Simulation Technique System - Brede, Melanie; Haange, Sven-Bastiaan; Riede, Susanne; Engelmann, Beatrice; Jehmlich, Nico; Rolle-Kampzczyk, Ulrike; Rohn, Karl; von Soosten, Dirk; von Bergen, Martin; Breves, Gerhard (Frontiers in Microbiology, 2022)
The use of the herbicide glyphosate and its formulations on protein-rich feedstuff for cattle leads to a considerable intake of glyphosate into the rumen of the animals, where glyphosate may potentially impair the 5-enolpyruvylshikimate-3-phosphate pathway of the commensal microbiota, which could cause dysbiosis or proliferation of pathogenic microorganisms. Here we evaluated the effects of pure glyphosate and the formulations Durano TF and Roundup® LB plus in different concentrations on the fermentation pattern, community composition and metabolic activity of the rumen microbiota using the Rumen Simulation Technique (RUSITEC). Application of the compounds in three concentrations (0.1 mg/L, 1.0 mg/L or 10 mg/L, n = 4 each) for nine days did not affect fermentation parameters such as pH, redox potential, NH¬3-N concentration, and production of short-chain fatty acids compared to a control group. Microbial protein synthesis and the degradation of different feed fractions did not vary among the treatments. None of the used compounds or concentrations did affect the microbial diversity or abundance of microbial taxa. Metaproteomics revealed that the present metabolic pathways including the shikimate pathway were not affected by addition of glyphosate, Durano TF or Roundup® LB plus. In conclusion, neither pure glyphosate, nor its formulations Durano TF and Roundup® LB plus did affect the bacterial communities of the rumen.